The relationship between Parity and the Occurrence of Chronic Energy Deficiency (CED) in pregnant women - HS, Senja Atika Sari; Nuri Luthfiatil Fitri; Uswatun Hasanah; Ludiana, Ludiana; Anik Inayati (Sean Institute, 2022)
Background: Pregnancy is an early process of life. Lack of energy intake from macronutrients and micronutrients results in chronic energy deficiency (CED) during pregnancy. The high prevalence of pregnant women with nutritional problems can have an impact on the health and safety of mothers and babies as well as the quality of babies born. Factors that cause pregnant women to experience CED is due to the consumption of less nutrients. However, increasing the incidence of CED in pregnancy can also be influenced by various factors, including infection factors, economic status, age, pregnancy distance, parity, knowledge, education level, employment status, and health services. The purpose of this study was to determine the relationship between parity and the occurrence of CED in pregnant women.Methods: The research of this study is an analytic cross-sectional design. The population of this study were pregnant women in the working area of the Ganjar Agung Public Health Center, Metro City. The Analysis using chi square test. Results: high risk parity found in 13 (12.0%) people and in. While the low risk parity found was 95 (88.0%). The results of the analysis of the different proportions test (Fisher's exact test) obtained a value of p = 0.030 (p <0.05); OR: 3.829 (CI; 95% 1.152-12.727), meaning that there is a relationship between parity and the incidence of CED in pregnant women where pregnant women who are at high risk parity (>4 children) have a 3,829 times.